2012
DOI: 10.1186/1880-6805-31-17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preceding exercise on cerebral and splanchnic vascular responses to mental task

Abstract: BackgroundTo investigate the effect of preceding acute exercise on the peripheral vascular response to a mental task, we measured splanchnic and cerebral blood flow responses to performing a mental task after exercise and resting.MethodsIn the exercise trial, 11 males exercised for 30 min on a cycle ergometer with a workload set at 70% of the age-predicted maximal heart rate for each individual. After a 15-min recovery period, the subjects rested for 5 min for pre-task baseline measurement and then performed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In addition, of the 29 studies 25 – 53 , only 4 (14%) included hypertensive patients 31 , 39 , 44 , 53 , 22 (76%) had a mean age of less than 30 years 25 30 , 32 – 34 , 37 , 40 43 , 46 , 50 52 , 54 56 , 4 (14%) were from 30 to 40 years old 35 , 38 , 47 , 48 , and only 4 (14%) were over 40 years old 31 , 39 , 44 , 53 . As for stress tests, we have as the most frequent the stroop color and word test (13 studies) 29 , 31 33 , 36 38 , 43 , 44 , 46 49 , followed by cold pressor 32 , 34 , 35 , 37 , 39 , 41 , 43 , 50 – 53 (11 studies), arithmetic test 25 , 27 , 29 , 30 , 39 , 40 , 42 , 45 , 48 (9 studies), public speaking (3 studies) 29 , 32 , 38 , handgrip (2 studies) 36 , 48 , and Trier Social Stress Test 28 and Study task 26 (1 study each). As for the time interval between the exercise session and the stressor task, only 2 studies (7%) performed more tha...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, of the 29 studies 25 – 53 , only 4 (14%) included hypertensive patients 31 , 39 , 44 , 53 , 22 (76%) had a mean age of less than 30 years 25 30 , 32 – 34 , 37 , 40 43 , 46 , 50 52 , 54 56 , 4 (14%) were from 30 to 40 years old 35 , 38 , 47 , 48 , and only 4 (14%) were over 40 years old 31 , 39 , 44 , 53 . As for stress tests, we have as the most frequent the stroop color and word test (13 studies) 29 , 31 33 , 36 38 , 43 , 44 , 46 49 , followed by cold pressor 32 , 34 , 35 , 37 , 39 , 41 , 43 , 50 – 53 (11 studies), arithmetic test 25 , 27 , 29 , 30 , 39 , 40 , 42 , 45 , 48 (9 studies), public speaking (3 studies) 29 , 32 , 38 , handgrip (2 studies) 36 , 48 , and Trier Social Stress Test 28 and Study task 26 (1 study each). As for the time interval between the exercise session and the stressor task, only 2 studies (7%) performed more tha...…”
Section: Resultsmentioning
confidence: 99%
“…As for stress tests, we have as the most frequent the stroop color and word test (13 studies) 29 , 31 33 , 36 38 , 43 , 44 , 46 49 , followed by cold pressor 32 , 34 , 35 , 37 , 39 , 41 , 43 , 50 – 53 (11 studies), arithmetic test 25 , 27 , 29 , 30 , 39 , 40 , 42 , 45 , 48 (9 studies), public speaking (3 studies) 29 , 32 , 38 , handgrip (2 studies) 36 , 48 , and Trier Social Stress Test 28 and Study task 26 (1 study each). As for the time interval between the exercise session and the stressor task, only 2 studies (7%) performed more than 60 min later 42 , 44 , 7 studies (24%) performed between 31 and 60 min later 29 , 32 , 35 , 40 , 49 , 53 , 54 and 23 studies (79%) performed in up to 30 min later 25 27 , 30 , 31 , 33 , 34 , 37 41 , 43 , 45 48 , 50 52 , 57 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since previous studies reported sustained changes in cerebral blood flow (CBF) up to 40 min following a single bout of moderate aerobic exercise (Smith et al, 2010;Someya et al, 2012;MacIntosh et al, 2014), which affects the BOLD (T2*) contrast in fMRI examinations, the acquisition of functional MIST-data started about 90 min after the exercise cessation. Thus, an influence of the mentioned CBF alterations on our stress-related BOLD response effects is unlikely.…”
Section: Mr-image Acquisitionmentioning
confidence: 99%